The relationship between physical activity and fear of childbirth with quality of life among pregnant women in Indonesia - Dewi Marfuah; Tukimin bin Sansuwito; Rathimalar ayakannu (Sahabat Publikasi Kuu, 2025)
Background: Physical activity and fear of childbirth (FoC) are recognized as influential factors on QoL. However, the interplay of these factors remains underexplored in the Indonesian context, where cultural and healthcare settings differ from high-income countries. Objective: To investigate the relationships between physical activity, fear of childbirth, and quality of life among pregnant women in Indonesia. Methods: This cross-sectional study involved 250 pregnant women recruited through convenience sampling from healthcare facilities in Indonesia. Data were collected using validated instruments: the Physical Pregnancy Activity Questionnaire (PPAQ), Wijma Delivery Expectation Questionnaire (WDEQ-A) for FoC, and Quality-of-Life Gravidarum (QOL-GRAV) questionnaire. Multiple regression analysis was employed to assess the relationships among physical activity, FoC, and QoL, adjusting for confounders. Results: The mean age of participants was 28.4 years (SD = 5.6), with 67.6% reporting moderate physical activity levels. FoC was prevalent, with 45.2% experiencing high levels, while 34.8% reported high QoL. Physical activity was positively associated with QoL (r = 0.52, p < 0.001), while FoC was negatively associated (r = -0.61, p < 0.001). Multiple regression revealed that physical activity (β = 0.39, p < 0.001) and FoC (β = -0.46, p < 0.001) were significant predictors of QoL, explaining 42.5% of the variance (R² = 0.425, p < 0.001). Conclusion: These findings underscore the importance of incorporating physical activity promotion and FoC mitigation into antenatal care to enhance maternal well-being.